2015
DOI: 10.1002/jib.242
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pitching rate on fermentation, maturation and flavour compounds of beer produced on an industrial scale

Abstract: The aim of the study was to determine the effect of the initial number of yeast cells in the wort on the process of fermentation, maturation and the content of the volatile components of beer, as well as the viability and vitality of the yeast biomass. The experiments were performed on an industrial scale, with fermentation and maturation in cylindro-conical fermentation tanks with a capacity of 3800 hL. Yeast for pitching was collected after secondary fermentation (third passage) and wort pitching levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
(39 reference statements)
2
7
0
3
Order By: Relevance
“…Acetaldehyde concentrations were only dependent on the pitching rate, with increasing amounts of acetaldehyde found at lower pitching rates ( Figure A1). This result correlates with other studies that found a decrease in acetaldehyde with increasing pitching rate in wort fermentations with brewers' yeasts [48,49]. However, overdosing yeast (>5 × 10 7 cells/mL) can lead to an increase in acetaldehyde again, as observed by Erten et al [50].…”
Section: Response Surface Methodology (Rsm)supporting
confidence: 91%
“…Acetaldehyde concentrations were only dependent on the pitching rate, with increasing amounts of acetaldehyde found at lower pitching rates ( Figure A1). This result correlates with other studies that found a decrease in acetaldehyde with increasing pitching rate in wort fermentations with brewers' yeasts [48,49]. However, overdosing yeast (>5 × 10 7 cells/mL) can lead to an increase in acetaldehyde again, as observed by Erten et al [50].…”
Section: Response Surface Methodology (Rsm)supporting
confidence: 91%
“…The sensory characteristics of beer are influenced by aromatic compounds formed by yeast during fermentation . The quantity of volatile compounds depends on the composition of the wort, aeration level, pitching yeast, process temperature and tank filling regime . The speed of the fermentation process is important in process control .…”
Section: Introductionmentioning
confidence: 99%
“…Higher fermentation temperature [27] Increased esters and alcohols Trub present in the fermenter [31,32] Reduced esters of increased alcohols Yeast nutrients added to wort [27] Increased esters and alcohols Increased wort oxygen at pitching [33] Reduced esters Pressure fermentation [34] Reduced esters, carbonyls and alcohols Higher wort gravity [12,35] Increased esters and alcohols Increased wort maltose [36,37] Decreased esters Increased wort lipids [38] Decreased esters …”
Section: Variable Possible Resultsmentioning
confidence: 99%